2020
DOI: 10.3390/ijerph17082674
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Proximity between Companion Dogs and Their Caregivers on Heart Rate Variability Measures in Older Adults: A Pilot Study

Abstract: Heart rate variability (HRV) is a noninvasive tool used to evaluate autonomic nervous system function and is affected by age, stress, postural changes, and physical activity. Dog ownership has been associated with higher 24-hr HRV and increased physical activity compared to nonowners. The current pilot study was designed to evaluate the effects of proximity to a dog in real time (minute-by-minute) on older dog caregivers’ HRV measures and stress index during normal daily life over a 24-hr period. Eleven caregi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…Actually, whether this physiological response is indicative of positive excitement or of potentially negative stress remains an open question. However, the observed positive effect (i.e., reduction) on systolic and diastolic blood pressure would seem to corroborate the hypothesis that human–animal interactions could contribute to improve the functioning of the cardiovascular system [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 52%
“…Actually, whether this physiological response is indicative of positive excitement or of potentially negative stress remains an open question. However, the observed positive effect (i.e., reduction) on systolic and diastolic blood pressure would seem to corroborate the hypothesis that human–animal interactions could contribute to improve the functioning of the cardiovascular system [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 52%
“…Many studies have demonstrated the association between pet ownership and cardiovascular health and dog owners appear to have a significantly greater chance of survival after a heart attack compared to people without pets [25][26][27]. Pets can therefore play an important role in reducing absenteeism and visits to family doctors or the hospital [28]. It has been estimated that pet ownership saved Australia $1 billion in 1994 [29], while it may reduce the use of the National Health Service (NHS) in the UK to the value of £2.45 billion per year [30].…”
Section: Positive Aspects Of Companion Animals For Humansmentioning
confidence: 99%
“…PetPace is a non-invasive collar designed for dogs and cats that allows real-time, continuous, remote monitoring of activity, temperature, pulse, respiration, variations in heart rate (HRV), position (lying, sitting, standing), and sleep quality (movement during sleep). The use of this collar was recently described in dogs and showed an excellent correlation with real-time variables ( 33 35 ). The results of increased activity following the liposomal CBD treatment in the dog presented here seemed to be correlated with owner subjective wellbeing evaluation and iVAS, although, this data should be interpreted with caution as other factors such as environmental conditions and owner activity can play a significant role in daily activity patterns.…”
Section: Discussionmentioning
confidence: 97%